Real-time human motion analysis and grasping force using the OptiTrack system and Flexi-force sensor - Saidon, Nur Farah Elya; Wada, Chikamune; Ahmad, Siti Anom; Abdul Rahman, Ribhan Zafira; Eguchi, Kiyotaka; Tomiyama, Yoshiyuki; Abd Rahman, Farida Izni (Universiti Putra Malaysia Press, 2017)
Biologically inspired robotic hands have important applications in industry and biomedical robotics. The grasping capacity of robotic hands is crucial for a robotic system. This paper presents an experimental study on the finger force and movements of a human hand during the grasping operation in real-time. It focuses on two topics; measuring grasping force using Flexi-force sensors and analysing human hand action during grasping operation. The findings show that lifting required higher forces compared with grasp force in the static phase.